The "Purification" for Multiagent Textile Production Manufacturing and Management System and Its Optimization Design. Issue 6 (27th April 2012) - Shao, Jingfeng; Liu, Sheng; Wang, Jinfu; Li, Yonggang; Liu, Haiping
Abstract To solve the backward status of the textile enterprise, which included the inefficiency of management work, the complexity of business process, and the isolation of business data, first, through using multiagent technology, a production manufacturing and management system structure model based on multiagents was proposed, the rationality of the model was introduced, and the existed production planning was optimized. Then, a flexible collaboration management platform was formed, which was for production manufacturing and management. Meanwhile, the correlation degree among production data was analyzed, and the influencing factors affecting the accuracy of production data was introduced via brittleness theory and fuzz C means clustering algorithm (FCM). Third, a coupling relationship model for analyzing influencing factor, and a dynamic quality performance model based on brittleness theory was designed, respectively. As proved in practice, the multiagent system has strengthened the interactivity of both the user and the system, met the requirements of production manufacturing and management, ensured the correctness of business data, achieved the heterogeneous integration of production data, and promoted the information development of the textile industry. © 2012 Wiley Periodicals, Inc.